Coaches' perception of catastrophic injuries risks in South African Rugby Union : A qualitative exploration through a socio-ecological lens - Joshua, Jonathan (MRC/UCT RU for Exercise and Sport Medicine, 2018)
Introduction: The annual rate of rugby-related catastrophic injuries (CIs) in South Africa has been classified as "acceptable". However, of all injuries, CIs are the most traumatic for all involved. Therefore, the BokSmart programme was introduced in South Africa to reduce CIs by training all coaches in safe coaching principles. South Africa presents a particularly difficult implementation context for injury prevention interventions due to large variations in socio-economic statuses (SES) of sport participants. In addition, individuals are known to accept perceived levels of risks and ignore the actual levels of risks. Thus, rugby policy makers, experts, coaches and players may have conflicting views regarding CIs risks associated with the sport. In rugby, objective measures of risks such as risk probability are well defined however; little is known about how rugby coaches perceive the risks of CIs in rugby. This is a concern for rugby governing bodies such as SARU because coaches' perceptions of CIs risks could play a role in their adoption of BokSmart coaching principles. Additionally, risk perceptions of South African rugby coaches may vary by SES. Socio-Ecological Models (SEM) give attention to the intrapersonal, interpersonal and societal influences that affect the perceptions of coaches from various SES settings. Using qualitative methods, the aim of this research was to explore South African rugby coaches' perceptions of CIs, through the lens of a SEM. Methods: Six semi-structured focus groups were conducted with junior and senior coaches from three tiers of SES settings: low, middle and high. An additional focus group was conducted with rugby referees' to corroborate evidence from the coaches' focus groups. For analysis, a thematic framework was developed based on factors that were found to influence risk perceptions from catastrophic event studies. Themes were: 1) SES, 2) Knowledge of rugby and CIs, 3) CIs experience, 4) Cognitive biases, 5) Attitudes and intentions, 6) Coach pressure, and 7) Mass media. Results and Discussion: This study's findings suggest that coaches' perceptions of CI risks vary according to SES. Low SES coaches predominantly implied that lack of adequate rugby infrastructure influenced beliefs that their players are at risks of CIs. For Middle SES coaches, lack of knowledge about CIs prevention influenced perceptions about their players' risks of CIs. Lastly, high SES coaches' were mainly influenced by cognitive biases, perceiving their players to be less vulnerable to CIs than players in lower SES settings. All coaches were influenced by 1) a lack of CIs experience that prompted perceptions of invulnerability to CIs, 2) 'win at all costs' attitudes and intentions, and 3) coaches' pressure, both of which lowered concerns for CIs risks and resulted in players 'playing on' despite injuries. In addition, the SEM provided the overall perspective of the ecological factors that influenced coaches' perceptions of CIs. Conclusion: Perceptions of CIs risk differ among coaches from various SES settings. Therefore interventions such as the BokSmart programme should be tailored towards targeting various SES groups.